Reliability of heart rate responses both during and following a 6 min Yo-Yo IR1 test in highly trained youth soccer players - Doncaster, G.; Scott, M.; Iga, J.; Unnithan, V. (Science and Medicine in Football, 2019)
Purpose: To examine the reliability of heart rate (HR) measures obtained during a 6-min Yo-Yo Intermittent Recovery Test Level 1 (Yo-Yo IR1), and following a 3-min passive recovery, within a group of highly trained youth soccer players Methods: Eight players completed three separate 6-min Yo-Yo IR1 tests, with a passive recovery, over a 2-week period. Measures of absolute heart rate (bpm) and relative HR (%HRmax) were obtained at the 3rd and 6th min of the test, with measures relative to the end HR (%HRend) 10, 20, 30, 60, 90, and 180 s, during the 3-min passive recovery. Variability in HR measures were assessed across successive trials (trial 1 vs. 2 and trial 2 vs. 3) and across all three trials, using the intraclass correlation coefficient (ICC), coefficient of variation (CV) and typical error (TE). Results: HR measures obtained during the 6-min Yo-Yo IR1 test displayed good levels of reliability (ICC: 0.95-0.98, CV: 1.1-1.3% and TE: 0.96-2.44). Results, display a potential learning effect, with lower levels of variability between trial 2 and trial 3. Examination of %HRend obtained during the passive 3-min recovery demonstrated an increased variance, as the passive-recovery period progressed. Conclusion: The 6-min Yo-Yo IR1 test presents a novel and potentially practical approach to regularly assessing youth soccer players` physical response to intermittent exercise. Practitioners and researchers should, however, consider the need for appropriate familiarisation when undertaking this test.